DETERMINATION OF PHYTOCHEMICAL CONSTITUENTS AND ANTIMICROBIAL ACTIVITY OF ANOGEISSUS LEIOCARPUS EXTRACTS - Kefas Ishaya Ambair; James Hamuel Doughari; Joel Uyi Ewansiha; Musa Sale Pukuma (International Journal of Pharmacy & Integrated Health Sciences)
Background: Plants are rich sources of biologically active formulations employed globally for decades as traditional remedies against various diseases. Objectives: In this study, the extraction yields, phytochemical constituents, number of fractions in each crude extract, and antimicrobial activity of extracts from leaves, stem, and root barks of Anogeissus leiocarpus were determined. Methodology: Extracts from samples of this plant's parts were serially and exhaustively extracted by maceration in solvents of increasing polarity viz n-hexane, chloroform, acetone, methanol, and water for 72 h with 8 hourly vigorous agitation at room temperature. Results: The result showed acetone leaves extract to have the highest yield of 23.66±0.38% and six fractions, while the phytochemicals screening of the extracts revealed the presence of phenols, tannins, flavonoids, terpenoids, steroids, alkaloids, and saponins. Antimicrobial activity showed root bark acetone extract to be the most active with diameter of zone of inhibition of 25.0+1.41 against Staphylococcus aureus, a minimum inhibitory concentration (MIC) of 0.313±0.00 mg/ml against Pseudomonas aeruginosa and Klebsiella pneumonia and a minimum bactericidal concentration (MBC) of 0.625±0.00 mg/ml against Pseudomonas aeruginosa and Klebsiella pneumonia. Results also showed the extract to be bactericidal and fungicidal with MBC/MIC and MFC/MIC ratios of less than four against all the test fungi, thus possessing both bactericidal and fungicidal activity. Conclusion: The high extract yields and antimicrobial activity shown alongside the presence of various phytochemical constituents in the extracts of Anogeissus leiocarpus justify its use as a remedy for many ailments in alternative medicine. Thus, the correlation between its phytochemical constituents and antimicrobial activity underscores the need to develop new antimicrobial compounds.